Mechanisms of impaired expression of p53-responsive microRNA genes in diffuse B-large cell lymphoma - E. N. Voropaeva; T. I. Pospelova; M. I. Churkina; A. A. Gurazheva; O. V. Berezina; V. N. Maksimov (Успехи молекулярной онкологии, 2023)
Introduction. A more in-depth description of molecular events that disrupt the functioning of the p53 signaling pathway is important for understanding the mechanisms of formation and progression of diffuse B-large cell lymphoma (DCCL), as well as its sensitivity to treatment. The p53 protein exhibits its oncosuppressive function and mediates the antitumor effects of drugs by regulating transcription and/or maturation of a wide range of target genes, including MIR-34A, MIR34B/C, MIR-129-2 and MIR-203. In the tumor tissue of lymphomas, in comparison with normal lymphoid tissue, a decrease in the level of microRNAs encoded by these genes is shown.Aim. The aim of this study was to conduct a comprehensive analysis of the methylation of the genes of the p53-responsive microRNAs MIR-34A, MIR-34B/C, MIR-203 and MIR-129-2, as well as mutations in the DNA-binding domain and destruction of the polyadenylation signal of the TP53 gene in DLBCL.Materials and methods. 136 DNA samples isolated from tumor tissue of patients with DLBCL and 11 DNA samples obtained from lymph nodes with reactive B-cell follicular hyperplasia were analyzed. The methylation status of MIR-203 and MIR-129-2 genes was determined by the method of methyl-specific polymerase chain reaction, MIR-34A and MIR-34B/C genes by the method of methyl-sensitive analysis of high-resolution melting curves. In tumor samples, rs78378222 genotyping was performed by polymerase chain reaction with restriction fragment length polymorphism, resulting in the destruction of the polyadenylation signal, and the nucleotide sequence of the region of the TP53 gene encoding the DNA-binding domain was determined by capillary direct sequencing by Sanger.Results. The methylation detected in lymphoma tissue was tumor-specific. The frequency of analyzed aberrations in the TP53 gene and methylation of MIR-34A, MIR-34B/C, MIR-129-2 and MIR-203 was 21, 23, 55, 65 and 66 %, respectively. At the same time, methylation of the analyzed genes of p53-responsive microRNAs and aberrations in the TP53 gene in the tumor tissue of patients with DLBCL were independent events with a tendency to mutual exclusion. At the same time, it was shown that in the vast majority of lymphoma samples, the methylation of the MIR-34A, MIR-34B/C, MIR-129-2 and MIR-203 genes was combined.Conclusion. Along with aberrations in TP53, methylation of MIR-34A, MIR-34B/C, MIR-129-2 and MIR-203 genes may be an important cause of decreased expression of miR-34a, miR-34b, miR-34c, miR-129 and miR-203 in DLBCL. The combined methylation of the MIR-203, MIR-129-2 and MIR-34B/C genes, as well as the MIR-34B/C and MIR-34A pairs, potentially has a more pronounced pro-tumor effect due to the presence of common targets in the microRNAs encoded by them.